Trajetórias de docentes nos cursos de formação: um estudo do percurso interdisciplinar e suas implicações na prática profissional - Lima, Márcia Helena de (2017)
This work is a study of the trajectories of teachers in training courses, with a focus on capturing the echoes of interdisciplinarity in the making, to respond to the need to broaden the discussion related to teacher training in Brazil. Aims search the interdisciplinary course teachers in training courses, with a view to their implications in professional practice. In this proposal, the problem of study is characterized by understanding how to build and if effective interdisciplinary in do. To respond to the goal and assumptions, seeks to investigate some of the theories that have influenced the teacher training, the conceptions related to interdisciplinarity, the laws and decrees of the early history of brazilian education until the present day and its impact on the formulation of concepts about interdisciplinarity in basic education. Takes as an assumption that professionalization is an aspect of the disciplinary or interdisciplinary experiences that can interfere in the school context. The study was based on literature search and utilizing research procedures, such as questionnaires and wheel of conversation. Finally, it concludes that the interdisciplinarity in the school will complement or overcome disciplinary practice, awakens a vision of totality of knowledge and encourages teachers to perception of the complexity of the world in which they are inserted. Its function is not to eliminate or overcome the disciplines, but increase the education with the holistic view of knowledge, considering also the disciplinary culture.